Retrospective study of 53 cases of caesarean myomectomy regarding its safety and feasibility - Mangala, Janu Kanthi; Sreedhar, Sarala; Sumathy, Sudha; B., Rajammal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: In recent era, many studies have come up stating the safety and feasibility of caesarean myomectomy. With the advances in surgical techniques, the risk is very minimum. Our primary objective is to evaluate the safety of caesarean myomectomy and to analyse the blood loss according to the size, site of fibroids and with various methods used to prevent blood loss and postoperative morbidity. Methods: Retrospective studies of 53 women were included in our study who underwent caesarean myomectomy in the period of June 2006 to June 2015. Site, Size and number of myomas removed were noted down. Hemoglobin difference between pre and postoperative levels also noted down. Results: There is no significant blood loss difference according to the type, number and methods used to prevent blood loss. But as the size increases, there is significant blood loss difference- P value 0.006. Conclusions: Caesaren myomectomy can be safely undertaken by experienced surgeons. Single or multiple, smaller subserosal and intramural myomas can be safely removed .Though larger fibroids have increased blood loss intraoperative, with the prophylactic measures, we can safely remove them too. Submucosal, cornual myomas have to be dealt with caution.